Penerapan QR-Code Untuk Presensi Mahasiswa Pada UIN Raden Intan Lampung Berbasis Android - Hendra Kurniawan Hendra; M. Zaky Fanany Zaky; Neni Purwati Neni; Sri Karnila Karnila (Politeknik Negeri Sriwijaya, 2022)
QR-Code is a form of identity technology or 2-dimensional identifier that functions to store information in it. The use of QR-Codes tends to be widespread compared to barcode technology. One of the uses of qr-code is in the student attendance activity of UIN Raden Intan Lampung. The use of QR-Code for the attendance of UIN Raden Intan Lampung students is due to the paper-based student attendance. The student attendance QR-Code is made with the aim of making it easier for lecturers or related parties to get student attendance data as a benchmark in providing quality scores or percentages of eligibility to take the exam. The student attendance system by applying the QR-Code is built using a system development model, namely a prototype model. Keywords— QR-Code, Student’s Attendance, Android, QR-Code Attendance